Annotated Translation of Thumbelina Fairy Tale - Frida Aprilia; Rini Adriati (ESENSI LINGUA, 2019)
This research focuses on annotated translation. The object of the research is a fairy tale titled Thumbelina, written by Hans Christian Andersen. The purpose of this research are (1) to attain information concerning the difficult problems faced by the researches during the translation process of the source text; (2) to give solutions to the difficult problems. The researchers took eight out of forty-four difficult problems which consists of words, phrases, idiom, and sentences. Those difficulties were solved by referring to translation procedures as stated by Peter Newmark, and supported by monolingual, bilingual, and thesaurus dictionaries ABSTRAK Penelitian ini berfokus pada terjemahan beranotasi. Objek dari penelitian ini merupakan sebuah dongeng berjudul Thumbelina, dikarang oleh Hans Christian Andersen. Tujuan dari penelitian ini adalah (1) untuk mendapatkan informasi mengenai problem sulit yang dihadapi oleh para peneliti selama proses penerjemahan naskah sumber; (2) memberikan solusi pada masalah-masalah sulit. Peneliti mengambil delapan dari empat puluh empat masalah sulit yang terdiri dari kata-kata, frasa, idiom, dan kalimat. Kesulitan-kesulitan itu diatasi dengan cara merujuk pada prosedur penerjemahan sebagaimana dinyatakan oleh Peter Newmark, dibantu oleh kamus-kamus eka-bahasa, dwi-bahasa dan thesaurus.